The Role Of Psychological Empowerment In Mediating The Influence Of Spiritual leadership On Asn Creativity - Arivatu Ni’mati Rahmatika; Bekti Widyaningsih; Kharisma Ruudlotul Falah (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of spiritual leadership on the creativity of State Civil Apparatus (ASN) personnel, with psychological empowerment serving as a mediating variable, at the Education and Culture Office of Jombang Regency. This is a quantitative study employing a survey method. Data were collected via questionnaires distributed to 60 ASN personnel selected as the research sample and subsequently analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results indicate that spiritual leadership has a positive but insignificant effect on ASN creativity. Conversely, psychological empowerment has a positive and significant effect on ASN creativity and successfully mediates the relationship between spiritual leadership and creativity. These findings suggest that enhancing ASN creativity is more effectively achieved by strengthening psychological empowerment supported by spiritual leadership practices. Therefore, the organization is advised to cultivate leadership oriented toward spiritual values ​​while simultaneously enhancing employees' perceived competence, autonomy, meaningfulness of work, and impact of work to foster creativity in the performance of duties. Future research is encouraged to expand the scope of the study and the number of respondents to achieve a higher level of generalizability.